Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Konsumsi Rumah Tangga Petani Di Kecamatan Pantai Cermin - Suwarni, Suwarni; Rahma, Tri Inda Fadhila; Harahap, Rahmat Daim (Jurnal Manajemen Akuntansi (JUMSI), 2024)
This research aims to determine and analyze the influence of income, number of family dependents and education on the level of consumption of farmer households in Pantai Cermin District. This study is a quantitative study with multiple Linear regression analysis. The Data in this study was obtained by distributing questionnaires with Slovin method so that 98 respondents who were in Pantai Cermin subdistrict. The results of this study indicate that the T-test of the income variable (X1) states that the income variable has a partial and significant effect on the level of household consumption of farmers, so as to prove that Ha is accepted and H0 is rejected. From the results of the T test states that the variable number of family dependents partially and significantly affect the level of household consumption of farmers, so it can prove that Ha is accepted and H0 is rejected. And for the results of the education variable t test stated no effect partially and significantly on the level of consumption of peasant households, so as to prove H0 is accepted and Ha is rejected. While the F test(simultaneous) shows that the variables of income, number of family dependents and education simultaneously affect the level of consumption of farmer households. From the test results of the coefficient of determination in the column R Square get a value of 0.482, the value of the coefficient of determination is changed in percentage to 48.2%. So it can be concluded that there are 48.2% of the consumption level of farmer households influenced by income, number of family dependents and education. While the remaining 51.8% were influenced by other factors studied in this study.